USE CLEANER PRODUCTION TECHNOLOGY TO REDUCE COSTS AND ACHIEVE PRODUCT SUSTAINABILITY STRATEGY/ APPLIED STUDY AT YOUR PUBLIC COMPANY IN DHI QAR - M.M. Mohammed Abdul Amir Al-Ghozi (Scholar Express Journals, 2022)
The production of cleaner production from concepts and modalities requiring by the economic and industrial units in particular for its prominent and important role in reducing costs and reducing environmental effects and achieving sustainable development strategy, because continuing and staying on traditional methods makes it difficult for the economic unit to stay and continue In a long-term competition environment, because of its high costs as well as the difficult processes as well as the difficulty of meeting the needs and desires of customers because most of customers are not aimed at getting goods and services that meet their needs only but seeking the environmental impact of environmental impacts for being They have become more awareness, so economic units should be aware and seeking to use modern technicals, methods and means that enable sustainable product strategy if cleaner production is one of the best ways and means that enable industrial economic units to provide sustainable products Toxic and reduce energy consumption, waste materials and reduce emissions and help to Waste ware, as well as the role of cleaning production in reducing costs incurred by Economic Unity during its full work and in particular environmental costs
Keywords: cleaner production technology; cleaner production; reduction costs; sustainable product strategy